A formação de profissionais em tecnologia da informação na área de desenvolvimento de software - Camacho Júnior, Carlos Olavo de Azevedo (2011)
This research aims to verify how application projects can help the software developer professional to acquire knowledge about the 3-tier development model. Nowadays companies want to prove that their services are accomplished with the best quality standards of information technology. To do that many tools are created and a special one is called IDE Integrated Development Environment. An IDE allows the software developer professional to bring efficacy into his project. We will discuss what skills are important to this professional. This research will analyze the question: Why do companies based on information technology like to use processes with patterns? To demonstrate the importance of patterns in technology field, we search the Internet history (Vint Cert, Demi Getsko) to discuss the patterns used in Internet history. We have written articles about .NET development to demonstrate how to use patterns in a software development project. This research originated a book titled "Desenvolvimento em Camadas com C# .NET (available in portuguese only)" who was used by IFET-SP students in a study. We´ll analyze this study to get indicators about the efficiency of application project in the educational process of the software developer professionals